2008
DOI: 10.1007/s00534-007-1277-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative biliary drainage for biliary tract and ampullary carcinomas

Abstract: We posed six clinical questions (CQ) on preoperative biliary drainage and organized all pertinent evidence regarding these questions. CQ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 30 publications
1
57
1
Order By: Relevance
“…The number of patients in our study was not significantly different from those in retrospective studies by Nagino et al (2008) and Kawakami et al (2011), in which the overall median survival times were approximately 5-9 months. This result was substantially different from that of a prospective randomized control trial from Thailand by Sangchan et al (2012) that reported a median survival time for unresectable CCA of only 1.3-4 months.…”
Section: Figure 2 Survival Curves Of Patients In the Present Studycontrasting
confidence: 74%
See 3 more Smart Citations
“…The number of patients in our study was not significantly different from those in retrospective studies by Nagino et al (2008) and Kawakami et al (2011), in which the overall median survival times were approximately 5-9 months. This result was substantially different from that of a prospective randomized control trial from Thailand by Sangchan et al (2012) that reported a median survival time for unresectable CCA of only 1.3-4 months.…”
Section: Figure 2 Survival Curves Of Patients In the Present Studycontrasting
confidence: 74%
“…This study compared the clinical manifestations of different CCA types in an Eastern population, and similar comparisons in Western populations were reported previously. This study revealed that weight loss occurs in as many as 85.8% of patients with CCA in Eastern populations, compared with a rate of 35% in Western populations, but the brush cytology positivity rate was similar between Eastern and Western populations (42.6% vs. 9-24%) (Klatskin, 1965;Nagino et al, 2008;Friman, 2011;Kawakami et al, 2011;Moon and Choi, 2011;Khan et al, 2012). In this study, serum CA19-9 levels exceeding 100 U/mL were detected in 54.0% of the patients.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…The Japanese Society of Hepato-Biliary-Pancreatic Surgery (JSHBPS) published the clinical practice guidelines for the management of biliary tract and ampullary carcinomas in 2008 [1][2][3][4][5][6][7][8][9][10]. This was the only clinical guidelines focused on these complicated diseases and contributed to provide general and specialized clinicians with knowledge on standard treatments.…”
Section: Introductionmentioning
confidence: 99%